IQ variability and cognitive life skills: insights from Spanish students in vocational physical activity and sports training - Madrid-Rísquez, María; Alcaraz-Rodríguez, Virginia; Gómez-Rey, Pilar; Muñoz-Llerena, Antonio (Frontiers in Sports and Active Living, 2025)
IntroductionThe increasing social and labor demand for technical professionals underscores the importance of vocational education in preparing students for the workforce. In the context of vocational education, Positive Youth Development can play a crucial role in enhancing students' cognitive and emotional life skills, which are essential for their overall development and future success.MethodsThe objective of this study was to analyze the development of four cognitive areas (verbal comprehension, perceptual reasoning, working memory, and processing speed) alongside the Full Scale Intellectual Quotient (FSIQ) in the Intermediate Vocational Training Program in Outdoor Activity Guidance in Córdoba, Spain, and its relationship with cognitive areas using the WAIS-IV test. The sample included 176 students aged 16 -29, who were administered questionnaires under controlled conditions to ensure clarity and accuracy.ResultsResults revealed that students generally scored below the population mean in overall IQ, with significant variability. Perceptual reasoning and working memory were average for most students, while verbal comprehension scores were predominantly low, and processing speed scores were very low. A moderate correlation was observed between FSIQ and verbal comprehension and perceptual reasoning, while processing speed showed a weak correlation.DiscussionThese findings highlight the challenges faced by vocational students, particularly in areas critical for learning. The study concludes that while intelligence levels in this group are diverse, many students fall below average, emphasizing the need for tailored educational support. Future research should explore targeted interventions to enhance cognitive performance and success in vocational education pathways.